Impact of music-based intervention on verbal memory: an experimental behavioral study with older adults - Diaz Abrahan, Verónika (2020)
Normal age-related declines have been reported in different cognitive functions, such as episodic memory. Some environmental factors have the potential to reduce cognitive decline and promote healthy aging. In this research, we employed musical improvisation as a focal music-based intervention to explore its effects as a modulator of verbal memory. We evaluated two types of verbal memory: a neutral one, employing the Rey Auditory Verbal Learning Test (Study 1), and an emotional one, implementing the Spanish version of Affective Norms for English Words (Study 2) in a volunteer group of older adults. After the acquisition of neutral (Study 1) or emotional (Study 2) verbal information, the participants were exposed to musical improvisation (experimental condition) or two control conditions (rhythmic reproduction as a musically active control condition or a rest condition as a passive control condition) for 3 min. Then, memory was evaluated through two memory tasks (immediate and deferred free-recall and recognition tests). In both studies, we compared memory performance among musicians (with five or more years of music training) and non-musicians. We found a significant improvement in neutral verbal memory among participants involved in musical improvisation, who remembered more words than those in the control conditions. Differences were also found according to the musical experience of the sample, with musicians outperforming non-musicians. The current research supports the late-life cognitive benefits of music-based intervention and music training.